Self-Perception of Digital Competences among Peruvian Teachers - Tomás-Rojas, Ambrosio (2021)
The study analyzes teachers’ self-perceived digital competence at a private university in Lima, Peru. A non-experimental comparative level design was used through non-parametric techniques. The DigCompEdu CheckIn tool of 25 items was applied with a Likert scale. The results indicate the need to (a) validate the questionnaire and have a measure of the construct with solid and stable psychometric properties; (b) compare these findings with those found in other MetaRed Peru institutions, as a point of contrast, to develop strategies that encourage teachers to continue their digital literacy; and (c) identify which interventions in informal settings help teachers develop their digital competence. © 2020 Copyright for this paper by its authors.